SANS (USH1G) Molecularly Links the Human Usher Syndrome Protein Network to the Intraflagellar Transport Module by Direct Binding to IFT-B Proteins - Sorusch, Nasrin; Yildirim, Adem; Knapp, Barbara; Janson, Julia; Fleck, Wiebke; Scharf, Caroline; Wolfrum, Uwe (Frontiers in Cell and Developmental Biology, 2019)
The human Usher syndrome (USH) is a retinal ciliopathy, characterized by profound congenital deafness, variable vestibular dysfunction and pre-pubertal onset of retinitis pigmentosa. In the effected sensory cells, USH protein networks are assumed to function in ciliary transport processes. The USH1G protein SANS is a scaffold of the ciliary/periciliary USH protein network of photoreceptor cells. Moreover, SANS is associated with microtubules, the transport routes for protein delivery towards the cilium. To enlighten the role of SANS in ciliary transport processes, we aimed to identify transport related proteins associated with SANS. The Intraflagellar transport (IFT) system is a conserved mechanism for bi-directional transport towards and through primary cilia. Thus, we tested the direct binding of SANS to IFT molecules, namely IFT20, IFT57, and IFT74 in 1:1 yeast-two-hybrid assay. The identified SANS-IFT interactions were validated in vitro via independent complementary interaction assays and in cells by applying membrane targeting assays. Immunofluorescence microscopy revealed the co-localization of SANS with IFT20, IFT52 and IFT57, respectively, at ciliary base and the connecting cilium of photoreceptor cells Our study demonstrated direct binding IFT complex B proteins IFT52 and IFT 57 to the N-terminal Ankyrin repeats and the central domain of SANS. This interaction provides direct evidence for a molecular link between the ciliary USH protein networks and the IFT transport module in primary cilia.